Audit Quality Control in Portugal: Longitudinal Study - Sara SERRA; Mariana LIMA; Kátia LEMOS (Communications of International Proceedings, 2020)
In Portugal, audit quality control is imposed on all audit firms. This requirement aims to improve the quality of the audit, and the decision-making process of stakeholders, who use the Audit Report. This article aims to analyze the results of the quality control of the audit, carried out in Portugal, using the content analysis technique of the Audit Quality Control Reports, issued between 2009 and 2019, by the Order of Statutory Auditors. The results indicate that, in horizontal control, there are deficiencies in the internal quality control systems, in the human resources used, and in the fulfillment of ethical requirements. In turn, in the vertical control, there are deficiencies in the execution of the audit work and the audit reports. This study, in addition to being innovative, contributes to raising awareness among audit professionals about the importance of quality audit practice.
Keywords: Audit Firms; Audit; Quality Control; Audit Quality Control Reports.